(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to assess the reality of activating social responsibility in the Arab Academy for Science, Technology and Maritime Transport in Lattakia, by addressing two basic dimensions (the organizational field- the academic field). The researcher relied on the comprehensive inventory method for the study community, by distributing (62) questionnaires to the scientific and administrative employees at the studied university, which were fully retrieved and analyzed. The researcher used T Student test for one sample as a basic test for this study to evaluate the reality of activating social responsibility. The research found a high level of the organizational field on the one hand, and a low level of the academic field in the studied university on the other hand. The research concluded with a set of recommendations related to the necessity of publishing the culture of social responsibility in university, and preparing an integrated work strategy for social responsibility, with the definition of employees with all its different dimensions.